Influência da adição de Co e Ni e da taxa de resfriamento na microestrutura de solidificação, nas propriedades mecânicas e na corrosão de ligas Al-Si-Cu-Zn-Fe - Xavier, Marcella Gautê Cavalcante (Universidade Federal de São Carlos, 2022)
An important strategy by 2050 will be to transform the production of recycled Al-Si alloys as a viable and sustainable source to reach the global demand for Al. The challenge will be to mitigate the deleterious effects caused mainly by the presence of the Fe element in these alloys. An alternative is to modify the composition of the alloy by adding a modifying agent and thus obtaining changes in its properties. Thus, this work examined two different alloy groups of typical industrial scraps: one representing low solute Al-Si alloys, Al-7%Si-0.6%Fe-0.35%Cu-0.25% Zn and another with a high solute content, Al-8%Si-0.8%Fe-2.5%Cu-1.0%Zn, (in wt.%). These alloys were independently modified using Co and Ni and evaluated regarding their as-cast structures. The presence of both Fe-contaning α and β phases was observed in samples solidified under cooling rates of about 10-1 a 102 oC/s by directional solidification (DS) and copper mold centrifugal casting, (C). High solute contents turned the Al-rich dendrites morphologies and, therefore, a substantial microstructural refinement was attained. Large range microstructure maps were obtained with λ1 and λ2 (35 µm – 502 µm; 4.3 µm – 31 µm, for low contents) and (37.5 µm – 331 µm; 10 µm – 32 µm, for high contents) associated with solidification thermal variables. The Co additions of 0.5 wt% and 0.7 wt%, reached higher values of tensile strength (201 MPa) without major losses in ductility (~10%). The corrosion resistance of the Al-7%Si-0.6%Fe-0.35%Cu-0.25%Zn-0.5%-Ni alloy was superior to the other tested alloys in conditions of long periods of exposure through immersion tests.
Influence of Co and Ni addition and cooling rate on the solidification microstructure, mechanical properties and corrosion of Al-Si-Cu-Zn-Fe alloys
Keywords: Ligas recicladas de Al; Solidificação; Intermetálicos de AlFeSi; Propriedades mecânicas de tração; Resistência à corrosão; Recycling aluminum alloys; Solidification; AlFeSi intermetallics; Tensile properties; Corrosion properties; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA